2005
DOI: 10.1136/adc.2004.061457
|View full text |Cite
|
Sign up to set email alerts
|

Dampened ventilatory response to added dead space in newborns of smoking mothers

Abstract: Background: Term newborns can compensate fully for an imposed dead space (tube breathing) by increasing their minute ventilation. Objective: To test the hypothesis that infants of smoking mothers would have an impaired response to tube breathing. Design: Prospective study. Setting: Perinatal service. Patients: Fourteen infants of smoking and 24 infants of non-smoking mothers (median postnatal age 37 (11-85) hours and 26 (10-120) hours respectively) were studied. Interventions: Breath by breath minute volume wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Our results are consistent with our previous findings that infants of mothers who smoked antenatally and were studied before maternity unit discharge had a dampened ventilatory response to added dead space, in which the major stimulus is hypercarbia when compared with control subjects (17). There are strengths and some limitations to our study.…”
Section: Original Researchsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with our previous findings that infants of mothers who smoked antenatally and were studied before maternity unit discharge had a dampened ventilatory response to added dead space, in which the major stimulus is hypercarbia when compared with control subjects (17). There are strengths and some limitations to our study.…”
Section: Original Researchsupporting
confidence: 91%
“…A similar magnitude of difference had been detected in the ventilatory response to added dead space, tube breathing, in which the main stimulus is hypercarbia (16) between newborns of smoking and nonsmoking mothers (17). See online supplement for additional information.…”
Section: Sample Sizementioning
confidence: 53%
“…In a previous study, 6 we demonstrated that the coefficient of repeatability of T c was 11 sec. Recruitment of 25 infants allowed, with at least 90% power at the 5% level, detection of a difference in the T c between positions of at least 11 sec.…”
Section: Sample Sizementioning
confidence: 75%
“…The coefficient of repeatability of T c had been previously shown to be 11 sec. 6 Respiratory muscle strength was then assessed by measurement of the maximum pressure generated during a multiple breath end expiratory airway occlusion (MIOP). During the procedure neck position was carefully controlled to avoid flexion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation